Nutritional literacy and health behaviors in primary school students in China: a cross-sectional study - Lu Liu; Xiuwen Ren; Weiwei Li; Suhua Zhao; Xiaoxiao Guo; Rui Yan; Xinjing Guo; Ronghua Li (BMC Public Health)
Abstract Objective The school-age children are in the stage of rapid growth and development, and balanced diet and rational nutrition is the basis for the normal development of children and even the health of their whole life. The study was designed to assess the nutritional literacy and health behaviors in Chinese primary school students. Methods A total of 5582 Chinese primary school students participated in the study. Self-designed questionnaire was used to collect the information of nutritional literacy and health behaviors. The students were divided into four groups based on their scoring rate in response to the scores answering the nutritional literacy questions. Results The overall scoring rate of answering the nutritional literacy questions was 0.89 for students in Grades 1–3 and 0.75 for those in Grades 4–6. Among students in Grades 1–3, the scoring rates of answering the questions related with dietary recommendations, food safety, characteristics of food, dietary habits, and nutrition and disease, were 0.82, 0.89, 0.95, 0.95, and 0.92, respectively. For the students in Grades 4–6, the scoring rates were 0.53, 0.85, 0.77, 0.81, and 0.89, respectively. Compared with G1 group, more students in the G4 group have the habit of having breakfast, and have higher frequency of consuming cereals, vegetables, fruits, meat, whole grain, and eggs, lower frequency of drinking sugary-sweetened beverages. And students in Grades 4–6 of G4 consumed less sea food. A positive correlation between the overall scoring rate and the frequencies of consuming breakfast, cereals, vegetables, fruits, meat, whole grain, and eggs was observed. Conversely, a negatively correlation between the overall scoring rate and the frequency of the sugar-sweetened beverages. Conclusion Emphasizing dietary recommendations in nutrition education for primary school students is necessary. Furthermore, higher nutritional literacy among Chinese primary school students is associated with greater dietary diversity and high frequency of breakfast consumption.